Estudio de factibilidad para la implementación de una empresa de lavandería de ropa (en agua), en la Ciudad de Zamora - Minga Ulloa, Tamia Isabel (2017)
This research is focused on the city of Zamora province of Zamora Chinchipe, the proposal is a research paper entitled " FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A LAUNDRY CLOTHES ( WATER ) IN THE CITY OF ZAMORA " . To fulfill the objectives , it has made the four studies, the same as detailed below: In the market study which allowed us to know that the city of Zamora there is an unmet demand for 130.978 kilos that wash a year , also there are three companies that provide service laundry in the city of Zamora they indicate that annually washed a total of 26.611 kilos. With increased of 12% In the technical study determined that the company will have an installed capacity to 332.880 kilos wash clothes corresponding to 23,74 % ( 79.040) of the installed capacity is 100 % capacity. In the study organizational and operational levels legislative, executive, consultant, assistant established for each of them have been established since depending on the functions used in each position. In the constitution the corporate name of the company is " Clean Clothes " Cia . Ltda . , Home will be in the city of Zamora in the streets Pio Jaramillo Alvarado and Sevilla de Oro corner , its duration is 5 years of life and its social objective is to offer the service laundry water to families in the city of Zamora. 6 In the financial study it determined that is required of $ 11.180,22 for the company to start its operation, to collect all that capital fund to $ 7.180,22 with own or outside capital which corresponds to 64.22 % and while that $ 4.000,00 will be financed through the credit union credit Ecuadorian Progressive Youth ( JEP ) corresponding to 35,78 % The production cost for year one is $ 37.765,93, with which a total of 69.160 kilos of clothes to wash , giving as unit production cost to $ 0,55 ctvs , that value we add 64 % margin useful , giving a total of 0,90 ctvs that will be the price charged the company for every kilo of washing clothes. Through the implementation of financial evaluation it has determined that the project is feasible , this by applying the financial indicators such as net present value which is $ 53.597,14 in the first year, the Period indicator Recovery Capital indicates that the investment is recovered , 8 months and 19 days, the internal rate of return is 142,92% , Benefit Cost ratio indicates that for every dollar invested in this company will have a gain of 0,69 cvts and sensitivity analysis with increased 47,20% in costs and decreased 28,30% in revenues